Religious language - Vainio, Olli-Pekka 1976- (Cambridge Cambridge University Press, 2020)
What does it mean to use language religiously? How does religious language differ from our ordinary linguistic practices? Can religious language have meaning? Among others, these questions are part of the so-called problem of religious language, which originates from the peculiar object of many religious claims, that is, the transcendent, or more precisely, God.
Title from publisher's bibliographic system (viewed on 11 Jan 2021)
Keywords: Language and languages -- Religious aspects; Language and languages ; Religious aspects